Analysis of SMEs Culinary Marketing Strategy During Covid 19 Pancemic: A Study at “Sate Bebek Cilegon” Resto in Cilegon, Banten - Marissa Grace Haque; Munawaroh Munawaroh; Denok Sunarsi (Peneliti.net, 2020)
The Covid 19 pandemic opens wider horizons of all of us, related to how to survive in the midst of business uncertainty and layoffs everywhere. Based on the theory of Basic Needs